Designing A Digital Marketing Strategy for Bumbu Instan Noeya Products using Sostac Method - Athfal, Muhammad; Wulandari, Sari; Aurachman, Rio (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
Bumbu Instan Noeya is a SME that is engaged in the culinary field, especially wet instant spices. Bumbu Instan Noeya sells its products through offline stores, supermarkets, and several social media and E-Marketplaces. Since the Covid-19 pandemic broke out in Indonesia, there has been an increase in sales through digital media by 26%, namely on Facebook media, but on other digital media there has been no increase in sales. This happened because the use of digital media on Noeya instant spices has not been optimal. This study aims to design a digital marketing strategy for Bumbu Instan Noeya products using the SOSTAC method which is organized into six stages, namely situation analysis, objective, strategy, tactics, action, and control. In this study, the results of the design of a digital marketing strategy obtained are the creation and optimization of social media (Social media Marketing) as a marketing and sales medium and other strategies, namely Social Media Optimization, Content Marketing, Video Marketing, Podcasts, Influencer Marketing, and User Generated-Content. In addition, Bumbu Instan Noeya is also working with several Instagram accounts that support products produced by MSMEs and will also open an online store through the E-Marketplace platform.